2018
DOI: 10.1097/dad.0000000000001117
|View full text |Cite
|
Sign up to set email alerts
|

CD34 and BerEP4 Are Helpful to Distinguish Basaloid Tricholemmoma From Basal Cell Carcinoma

Abstract: Tricholemmoma, a benign follicular neoplasm with outer root sheath differentiation, typically comprises clear or pale cells, and when multiple is pathognomic of Cowden's syndrome. The tumor is probably underrecognized and in basaloid examples can be difficult to distinguish from basal cell carcinoma (BCC). We studied 55 tricholemmomas (including 15 basaloid cases) and compared immunohistochemical profile with nodular BCC from our archives. Basaloid and non-basaloid tricholemmomas had similar staining character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…TC loses CK15 and 16, contrary to tricholemmoma, which might correlate with malignant transformation of tricholemmoma to TC. Tricholemmomas show upregulation of CD34 expression without BerEP4 expression, which may be distinguishing between this tumor and basal cell carcinoma [ 57 , 58 ]. Lectin UEA-1 (Ulex europaeus agglutinin 1) is strongly positive in outer root sheath cells and TC but is not observed in SCC, BCC, actinic keratosis, or porocarcinoma.…”
Section: Tumors With Follicular Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…TC loses CK15 and 16, contrary to tricholemmoma, which might correlate with malignant transformation of tricholemmoma to TC. Tricholemmomas show upregulation of CD34 expression without BerEP4 expression, which may be distinguishing between this tumor and basal cell carcinoma [ 57 , 58 ]. Lectin UEA-1 (Ulex europaeus agglutinin 1) is strongly positive in outer root sheath cells and TC but is not observed in SCC, BCC, actinic keratosis, or porocarcinoma.…”
Section: Tumors With Follicular Differentiationmentioning
confidence: 99%
“…Trichilemmoma is a benign follicular tumor with differentiation toward the outer root sheath of the pilosebaceous follicular epithelium, developing slowly over months to years [ 57 , 75 ]. Nature and pathogenesis have been a matter of debate for a long time; however, activating HRAS mutations, not only the same which occur in naevus sebaceous’ genotype, are carried; thus, molecular evidence indicates that most trichilemmomas are authentic neoplasms [ 22 ].…”
Section: Tumors With Follicular Differentiationmentioning
confidence: 99%
“…[9][10][11][12] BerEp4 and CD34 immunostains have previously been reported to aid in the distinction between trichilemmoma and BCC with focal expression of BerEP4 rarely identified in trichilemmoma compared with .50% tumor cell staining in most BCC and with focal expression of CD34 in most trichilemmomas compared with negative staining in BCC. 13 However, the cohort in their study was restricted to nodular BCC and expression of CD34 has been demonstrated in BCC in other studies. 14 Kurokawa et al 15 examined the expression of various cytokeratins, including CK17, in 3 cases of trichilemmoma and demonstrated CK17 staining in suprabasal cells of tumor nests.…”
Section: Discussionmentioning
confidence: 88%
“…27 In dermatopathology, CD34 has proven helpful in the distinction between trichilemmoma (positive) and BCC (negative). 28 Because different patterns of differentiation may reflect diverse pathogenetic mechanisms of genetic pathways and epigenetic changes, this study may contribute to better understand the pathogenesis of BCCs according to their underlying risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…27 In dermatopathology, CD34 has proven helpful in the distinction between trichilemmoma (positive) and BCC (negative). 28…”
Section: Introductionmentioning
confidence: 99%